Association between Serum 25-Hydroxyvitamin D Level and Stroke Risk: An Analysis Based on the National Health and Nutrition Examination Survey - Lan Wang; Shu Li; G. H. Anuja Sanika; Jinsheng Zhao; Hui Zhang; Lin Zhao; Wenfeng Wang (Behavioural Neurology)
Background. To analyze the association between serum 25-hydroxyvitamin D level (25(OH)D) and stroke risk based on the National Health and Nutrition Examination Survey (NHANES). Methods. Between 2007 and 2018, the baseline information of participants from NHNES was collected. Univariate analysis was used to identify the covariates. Multivariate logistic regression model was used to analyze the association between serum 25(OH)D level and the stroke risk. Results. Of the 8,523 participants, there were 310 participants with stroke and 8,213 participants without stroke. The multivariate logistic analysis showed that serum 25(OH)D deficiency (odds ratio (OR): 1.993, 95% confidence intervals (CI): 1.141-3.481, and P=0.012) was the significant risk factors for stroke. Subgroup analysis showed that non-Hispanic whites with serum 25(OH)D deficiency (OR: 2.501, 95% CI: 1.094-5.720, and P=0.001) and insufficiency (OR: 1.853, 95% CI: 1.170-2.934, and P=0.006) were associated with a higher risk of stroke than those with normal 25(OH)D levels. Conclusions. Serum 25(OH)D deficiency may be associated with an increased risk of stroke.